Feasibility of using olive biomass bottom ash in the sub-bases of roads and rural paths. (30th August 2018) - Cabrera, M.; Rosales, J.; Ayuso, J.; Estaire, J.; Agrela, F.
Highlights: We show the use of biomass bottom ash for soil treatments. Different mixtures of expansive soils were applied, with different BBA rates. The use of BBA as stabilizer material in road was proved. The addition of BBA in all the mixtures improved the bearing capacity. BBA reduces the expansion same as treatment whit lime. Abstract: Clay soils are widely distributed throughout the world and are the source of multiple technical problems in their application for the construction of sub-grade and sub-road bases. These types of soils are found in areas where civilian infrastructure such as roads and rural roads must be built. Therefore, in many situations it is necessary to use stabilized expansive soils, in the formation of the foundation and structural layers of linear infrastructures. Soil stabilization is used to increase the load capacity of the soil, and mixtures of lime and cement are generally used as binders. In recent years, interest in the recycling of industrial products and by-products has increased. One example of this is the use of biomass combustion in power plants. The management of significant amounts of waste (biomass bottom ash) from biomass power plants remains a problem. This paper presents the results of an experimental study for stabilizing expansive soil to determine its bearing capacity and mechanical properties via a triaxial test of the addition of biomass bottom ash. A double objective was targeted: reduction of the problems in using this type of soil and provision of a use for this type of waste. The results showed significant improvements in the mechanical. Therefore, herein is proposed the use of biomass bottom ash as a stabilizing agent for expansive soils, to improve the efficiency of the construction process by incorporating this product into a second life cycle as road bases.